Exporting Antiquities and Protecting Monuments: Beginnings of Ottoman legislation on the protection of ancient heritage as recorded by Polish travelers - Dominika Dziewczopolska (Studies in Ancient Art and Civilization)
In the 19th century, the number of European travelers visiting the Anatolian Peninsula and Constantinople was on the increase. The interest they took in the Greek-Roman past of these areas resulted in intensive digging of the ancient sites and led to the illegal exportation of monuments to Europe. In an attempt to stop this illegal practice, the authorities of the Ottoman Empire made efforts to implement modern law-making. Consequently, new legal acts were introduced in 1869, 1874, and 1884. These documents testify to the evolution in attitudes toward the protection and maintenance of heritage. Changes that occurred also involved the development of museology. The written accounts of Polish travelers provide an opportunity to trace how the legalities were (or were not) implemented and enforced. These testimonies offer, though in a somewhat sketchy manner, insight into the birth and growth of antiquities collection in the first Ottoman museum.